2019
DOI: 10.1080/21642850.2019.1612750
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experience with peer counselling and social support during a lifestyle intervention among women with a previous gestational diabetes pregnancy

Abstract: Purpose: Women who are diagnosed with gestational diabetes mellitus have an increased risk of developing type 2 diabetes, but most receive little guidance regarding disease prevention. This study examined the role and usefulness of social support, including peer counselling in facilitating behaviour change as a part of a healthy eating and physical activity intervention among women with a previous gestational diabetes mellitus pregnancy. Methods: We used a qualitative descriptive approach to investigate partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Previous studies have reported varying views regarding the best timing for intervention: some suggest during pregnancy [17,27,28] while others suggest postpartum [17][18][19]. We concluded that women with GDM should be prepared for more specific follow-up interventions such as those described above during their pregnancy, provided that this is done in a sensitive manner, echoing the findings of Ingstrup et al regarding the importance of rapport with peer councillors [29]. In general, any healthcare professional involved in the care of women with GDM can promote a longer-term perspective.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have reported varying views regarding the best timing for intervention: some suggest during pregnancy [17,27,28] while others suggest postpartum [17][18][19]. We concluded that women with GDM should be prepared for more specific follow-up interventions such as those described above during their pregnancy, provided that this is done in a sensitive manner, echoing the findings of Ingstrup et al regarding the importance of rapport with peer councillors [29]. In general, any healthcare professional involved in the care of women with GDM can promote a longer-term perspective.…”
Section: Discussionsupporting
confidence: 51%
“…60 These findings suggest future mHealth development should consider inclusion of existing online spaces women value in order to meet needs such as peer support, which have been found to impact women's ability to self-manage 61 and support behavior change. 62 Building on the findings of Chen et al, this review included six studies evaluating the effectiveness of mHealth systems for self-management of BGC. In accordance with NICE guidelines 63 evaluations typically adopted RCT designs to measure the ability of mHealth to improve glycemic control in comparison to standard care.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the mismatch between postpartum women’s preferences for lifestyle support and current practice. From the preferences that women discussed it seems that there is a need for postpartum lifestyle interventions to shift from focusing on the provision of didactic information to teaching practical strategies to mitigate barriers to healthy lifestyle behaviours [ 31 ]. Such strategies could include meal planning and preparation ideas, how to use seasonal fruits and vegetables to minimise cost, cooking healthy on a budget, time management, and motivational tools such as reminders, self-monitoring, and reinforcement [ 13 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both interview and survey findings suggest that social support for childcare, cooking, and physical activity is an important component of lifestyle programs for postpartum women [ 31 ]. Social support is very important for healthy eating and engaging in regular physical activity in all population groups and especially for postpartum women because of the challenges of caring for an infant [ 13 , 31 , 35 ]. Previous studies have shown that mothers that feel well supported were more likely to engage in healthy lifestyle behaviours than those who did not feel supported [ 31 , 35 ].…”
Section: Discussionmentioning
confidence: 99%